2009
DOI: 10.1093/jnci/djp019
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid and Risk of Prostate Cancer: Results From a Randomized Clinical Trial

Abstract: Data regarding the association between folate status and risk of prostate cancer are sparse and conflicting. We studied prostate cancer occurrence in the Aspirin/Folate Polyp Prevention Study, a placebo-controlled randomized trial of aspirin and folic acid supplementation for the chemoprevention of colorectal adenomas conducted between July 6, 1994, and December 31, 2006. Participants were followed for up to 10.8 (median = 7.0, interquartile range = 6.0-7.8) years and asked periodically to report all illnesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
200
3
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(217 citation statements)
references
References 24 publications
5
200
3
7
Order By: Relevance
“…Although folate deficiency has been linked to cancer susceptibility via increased uracil misincorporation (10), recent evidence suggests that high intake (Ն1 mg/d) of FA may exacerbate some preexisting cancers or progression of precancerous lesions, such as in the colon (11) or prostate (12). The activity of natural killer cells has been reported to be decreased in older women having higher plasma levels of unmetabolized FA (13).…”
mentioning
confidence: 99%
“…Although folate deficiency has been linked to cancer susceptibility via increased uracil misincorporation (10), recent evidence suggests that high intake (Ն1 mg/d) of FA may exacerbate some preexisting cancers or progression of precancerous lesions, such as in the colon (11) or prostate (12). The activity of natural killer cells has been reported to be decreased in older women having higher plasma levels of unmetabolized FA (13).…”
mentioning
confidence: 99%
“…Alternatively, folic acid supplementation may prevent malignant cell transformation on the one hand, but maintain the high cell proliferation rate that is characteristic in neoplastic cells on the other (16)(17)(18). From an epidemiological perspective, the largest randomized trial comparing folic acid supplementation versus placebo showed a higher risk of prostate cancer in men receiving folic acid supplementation, though this was a secondary outcome (4). The same results were not seen in large observational cohort studies where folate was not associated with prostate cancer (10,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of folate in prostate cancer carcinogenesis is very controversial (3). There is evidence suggesting dietary folate may be protective against prostate cancer while folic acid supplementation may promote cancer (4).To date, no studies have examined the role of folate in prostate cancer recurrence after primary treatment.…”
Section: Introductionmentioning
confidence: 99%
“…especially in the prostate, probably because of the increased availability of folate for the faster nucleotide synthesis of tumor cells. 17 For now, the majority of human studies indicate that dietary folate is protective against colon cancer.…”
Section: Micronutrientsmentioning
confidence: 99%